Soret/Dufour, variable density, and viscous dissipation effects on heat and mass transfer of Oldroyd-B fluid flow over polymer sheet with convective heat flux - Zia Ullah; Md. Mahbub Alam; Farida Safdar; Moataz Alosaimi; Feyisa Edosa Merga (AIP Advances)
This study explores the influence of viscous dissipation and variable density on heating efficiency and mass flux in magneto-hydrodynamic Oldroyd-B fluid flow over a polymer stretching surface with Soret and Dufour effects. The heat convective boundary conditions are used for the increment of thermal sequence. To incorporate nonlinear partial differential equations into a standard differential scheme, the appropriate transformation is used. The flow equations are reduced to nonlinear differential expressions and then numerically solved using the effective Keller box approach. The Newton–Raphson approach is applied to calculate the unknown quantities over the polymer sheet. The evaluation of the controlling flow factors, such as Prandtl quantity Pr, Deborah numbers β1, β2, Biot number γ, mixed convection parameter λ, magnetic parameter M, Eckert parameter Ec, on thermal distribution, mass distribution, and velocity profiles is calculated significantly. It is observed that a significant increase in the fluid temperature is evaluated at a minimal Prandtl number Pr = 1.5 but a maximum value is observed at a larger magnetic factor M = 3.5. Skin friction and the rate of mass flux are increased at a higher choice of heat convection parameter.